Pollen assemblages in Tamarix cone sediments and their implications for environmental change in the Southeastern Qaidam basin over the past 600 years - Hou, Xinyu; Zhao, Yuanjie; Guo, Xiaoqian; Song, Shaoteng; Feng, Yang; Dong, Yaqing (Frontiers in Plant Science, 2025)
IntroductionThe Qaidam Basin is situated in the transitional zone between Kunlun Mountains and Qilian Mountains as well as in China’s low-to-mid-latitude monsoon transition zone. The absence of conventional climatic information carriers has posed significant challenges for environmental change studies in this region. The pollen assemblage in Tamarix cone sediments serves as an effective proxy carrier for reconstructing the climosequence in arid areas.MethodsThis study employed 14C and 210Pb dating, pollen assemblages from a sampling site with pollen samples of Tamarix cone sediments, and principal component analysis (PCA) and quantitative paleoclimate reconstruction to reconstruct climatic and environmental changes in the Nuomuhong area from 1444 to 2022 AD.ResultsThe pollen is mainly comprised of herbs and shrubs, with a desert shrub vegetation type dominated by Artemisia, Chenopodiaceae, Nitraria, and Poaceae. Environmental changes are strongly correlated with soil salinity, the temperature of the warmest month (MTWA), the mean annual temperature (TANN) and the temperature of the coldest month (MTCO). Additionally, the changing trend of soil salinity was reconstructed based on the content of Nitraria. The following four zones are identified: 1) 1444–1520 AD, had high salinity and was humid (MTWA of 18.6–21.4 °C, TANN of 5.2–7.1 °C, and MTCO of -10.4–-8.9 °C); 2) 1520–1617 AD, with lower salinity and a humid conditions (MTWA of 16.0–19.4 °C, TANN of 3.1–5.8 °C, MTCO of -11.3–-9.6 °C); 3) 1617–1821 AD, with progressive aridification with reduced salinity (MTWA of 16.5–17.4 °C, TANN of 3.5–4.1 °C, MTCO of -11.5–-10.9 °C); and 4) 1821–2022 AD, with increasing salinity and a drier conditions (MTWA of 17.7–19.2 °C, TANN of 4.1–5.5 °C, MTCO of -11.3–-9.8 °C).DiscussionThe environmental changes may be associated with climate and groundwater variations induced by the Little Ice Age. Our findings provide implications for climate reconstruction and studies on environmental change in the Qaidam Basin and other arid regions with strong interannual variability.